Object based data fusion of landform and ancillary data for upscaling soil-landscape mapping in the western Australian pastoral rangelands - Wilson, Deanna; Corner, Robert; Schut, Antonius (IEEE, 2012)
We have investigated methods to derive landform and vegetation data from a Digital Elevation Model and remote sensing, using classification and segmentation. These data are required to upscale existing regional level landsystem mapping to a higher spatial and thematic resolution (subsystems). In turn the land subsystem data will be used to support rangeland condition mapping in a large area of leasehold rangeland. The derived landform and vegetation classes have been tested against available landsystem mapping derived by conventional methods and have shown promising relationships. These classifications need to be further revised prior to their use in either an object based or probabilistic classifier.